The books behind the masks: sources of warfare leadership in Ancient Egypt - Spalinger, Anthony John (Culture and history of the ancient Near East, 2021)
In The Books behind the Masks Anthony Spalinger continues his work on the warrior kings of pharaonic Egypt. Here is covered their actual war records from the perspective of literature and the contemporary court-based society, especially with the eulogies.